2004
DOI: 10.1111/j.1440-1843.2004.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved activities of daily living, psychological state and health‐related quality of life for 12 months following lung volume reduction surgery in patients with severe emphysema

Abstract: Lung volume reduction surgery improves not only lung function and exercise performance but also ADL, HRQL and psychological state for at least 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…We also reported that the psychological state scores did not significantly change up to 12 months after LVRS compare to the baseline (Goto et al 2004). Previous studies also showed that LVRS did not significantly improve the psychological evaluation scores, for examples, in the emotional reaction and mental health scores of the Nottingham Health Profile (NHP) by Cooper et al (1996), nor in the role emotional and mental health scores of SF-36 by Moy et al (1999).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We also reported that the psychological state scores did not significantly change up to 12 months after LVRS compare to the baseline (Goto et al 2004). Previous studies also showed that LVRS did not significantly improve the psychological evaluation scores, for examples, in the emotional reaction and mental health scores of the Nottingham Health Profile (NHP) by Cooper et al (1996), nor in the role emotional and mental health scores of SF-36 by Moy et al (1999).…”
Section: Discussionmentioning
confidence: 61%
“…One of the reasons may be that COPD is the progressive disease, and it is difficult for COPD patients to expect long lasting beneficial effects of LVRS. Indeed, lung function appears to improve in the first few months following LVRA in most patients, maximizing at approximately 3 to 6 months and declining thereafter (Brenner et al 1998;Goto et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…There is a great deal of research literature regarding indicators as measures of "quality of life." Two of these indicators are ability to perform activities of daily living (i.e., Goto et al, 2004) and geriatric literature reporting that independent mobility is an important factor in geriatric "quality of life" (i.e., Weismann, Eisfeld, Hanrich, & Hirtz, 2004).…”
mentioning
confidence: 99%